The Moderating Effect of Environmental Dynamism on Managerial Ownership, Risk, and Performance - Levana Dhia Prawati; Martinus Hanung Setyawan (Binus Business Review, 2016)
The goal of this research was to examine the effect of managerial ownership and risk toward company performance with company environment as the moderating variables and the firm-size as the control variable. The hierarchical cluster analysis was used to acquire two group samples of prospector and defender company. The result of multiple regression analysis shows that company environment moderates the risk and the managerial ownership toward the performance. Polynomial regression analysis method was conducted to test the effect of managerial ownership and risk toward the performance in the company with the type of prospector and defender. The result shows that in the prospector company, managerial ownership statistically does not give significant influence to company performance, and in the second degree, managerial ownership does not affect the company performance. This research also proves that managerial ownership negatively affects company performance in the defender company, although this influence gradually changes into the positive influence. This research reveals that risk gives positive influence to company performance in the defender company. Moreover, this influence gradually changes into negative influence. On the other hand, the risk gives negative influence to the performance of prospector company, and it gradually changes into the positive influence.